1997
DOI: 10.1149/1.1838187
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Phase Processing of Hydrophilic Features on a Silicon Wafer

Abstract: The four distinct stages of silicon wafer processing which are relevant to features such as trenches, vias, and topology are: (1) feature wetting, (2) chemical transport into and (3) out of the feature, and (4) feature drying. The present investigation is focused on hydrophilic surfaces. The time scales on which the mechanisms dominating these stages occur have been established. These time scales, while different, are nevertheless significantly shorter than the process time scale. In addition to that, the dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This could be because surface tension prevents the interface from deforming as necessary (De Gennes et al, 2004), the material to be cleaned has poor wettability, or dead-end structures do not allow gas to escape. For these reasons, a number of trials have investigated gas dissolution (Olim, 1997), the use of supercritical fluids (Ota and Tutsumi, 2008), and the wettability and influence of dissolved gas (Ota and Tutsumi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This could be because surface tension prevents the interface from deforming as necessary (De Gennes et al, 2004), the material to be cleaned has poor wettability, or dead-end structures do not allow gas to escape. For these reasons, a number of trials have investigated gas dissolution (Olim, 1997), the use of supercritical fluids (Ota and Tutsumi, 2008), and the wettability and influence of dissolved gas (Ota and Tutsumi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We measured the gas column area S G and liquid entering area S L using MATLAB before and after irradiation by acoustic waves. Equation (1) shows the definition of r.…”
Section: Methodsmentioning
confidence: 99%
“…Cleaning, painting, and bonding using liquids are indispensable in product manufacturing. To completely achieve these processes, the inside of surface holes must be filled with liquid [1][2][3]. This is easy in a through-hole or larger diameter hole due to capillary action or Rayleigh-Taylor instability.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been reported that attempt to model liquid-phase processes and the various steps of the process mechanism, but those that have been reported [2][3][4][5][6] generally neglect this first step by assuming that complete surface wetting occurs instantaneously. However, this assumption can be invalid: wetting is obstructed in features such as high-aspect-ratio vias and trenches, and on surfaces that exhibit a high contact angle in contact with process liquids, i.e., organic polymer dielectrics in contact with aqueous solutions.…”
mentioning
confidence: 99%
“…A recent analysis 6 investigates the wetting mechanism but concludes that wetting time is an insignificant contributor to total processing time; for example, a 0.5 m wide feature with a height of 4 m was estimated to fill in less than 1 s. 6 This study was performed for specific liquid properties in the limit of steady-state transport dominated by diffusion only in the feature. The time dependence of wetting and the resistance to mass transfer outside the feature are neglected.…”
mentioning
confidence: 99%